Apoptosis and cell cycle mechanisms of ampelopsin E on triple negative breast cancer cells - Abd Rahman, Napsiah (2017)
Cancer remains as the second leading cause of death after cardiovascular disease, worldwide. Approximately 14.1 million new cancer cases and 8.2 million cancer deaths were reported in 2012. Breast cancer is the most common cancer among women with 522,000 deaths in 2012 alone. There are a few treatment modalities for breast cancer that include chemotherapy, mastectomy, biological therapy and hormone replacement therapy. Chemotherapy remains as the main treatment, but it comes with severe side effects such as immunosuppression and formation of secondary tumor. Therefore, people now are turning to natural products that include the use of plant as an alternative for management of the cancer. Indeed, plants have been a good source of a few anticancer drugs such as taxol, vincristine and vinblastine. Dryobalanops or also known as Kapur can be found in tropical rain forest of West Malesia (Peninsular Malaysia, Borneo and Sumatra). There are only seven species of Dryobalanops, which are D. rappa, D. aromatica, D. lanceolata, D. beccari, D. fusca, D. keithii and D. oblongifolia. Resveratrol oligomer is a major group of bioactive compounds that can be found in Dryobalanops species was reported to exhibit antioxidant, antifungal, anti-HIV, anti-platelet aggregation, tyrosinase and cyclooxygenase I and II inhibitory properties. The objective of this study was to determine the cytotoxicity of resveratrol oligomers (ampelopsin E, ampelopsin F, flexuosol A, laevifonol, Malaysianol A, Malaysianol D and nepalensinol E) from Dryobalanops species towards non-hormone dependent (MDA-MB-231) and hormone dependent (MCF-7) breast cancer, human colorectal adenocarcinoma cancer (HT-29), alveolar carcinoma (A-549), cervical adenocarcinoma (HeLa), non-tumorigenic epithelial breast (MCF-10A) and mouse embryonic fibroblast (NIH/3T3) cells. The cytotoxicity was determined by MTT assay. The cells were treated with the compounds (0.94-30 μM) for 72 hours. The mode of cell death was evaluated by using an inverted light microscope and annexin V/PI flow-cytometry analysis. Cell cycle analysis was performed by using a flow cytometer. Effects of ampelopsin E on the expression of NF-κB, p53, p21, Cyclin A, Cyclin B1, CDK1, Bax and Bcl-2 were analysed by using Western blotting. Data showed that ampelopsin E was most cytotoxic towards MDA-MB-231 cells with the IC50 (50% inhibition of cell viability compared to the control) of 14.5±0.71 μM. Cell shrinkage, membrane blebbing and formation apoptotic bodies characteristic of apoptosis were observed following treatment with ampelopsin E. The annexin V/PI flow cytometric analysis further confirmed that ampelopsin E induced apoptosis in MDA-MB-231 cells. Cell cycle analysis revealed that ampelopsin E induced G2/M phase cell cycle arrest in the cells. The expression level of Bax and p21 was significantly up-regulated (p<0.05), whereas, the expression level of NF-κB, p53, Cyclin A, Cyclin B1, CDK1 and Bcl-2 was significantly down-regulated (p<0.05) after treatment with ampelopsin E. In conclusion, ampelopsin E induced apoptosis and cell cycle arrest in MDA-MB-231 cells. It is postulated that the induction of apoptosis is via NF-κB p53/p21 and intrinsic pathways, and the G2/M arrest is via p53-independent/p21 pathway. Therefore, ampelopsin E has the potential to be developed into an anticancer agent for the treatment of triple negative breast cancer.